Gambaran Sanitasi Dasar Pengelolaan Limbah Rumah Tangga di Kecamatan Kaliwates Kabupaten Jember - Prehatin Trirahayu Ningrum (Fakultas Kesehatan Masyarakat, Universitas Jember, 2013)
Elementary sanitation is minimal requirement senviron mental health that must beowned by every family to meet their daily needs. The scope of basic sanitary facilities are water supply, house hold toilets, waste disposal facilities, and waste water disposal. Fromthe data, there are three primary health centers Kaliwates are as have a higherpercentage of owner shipbins and toilets are low. Workupexamined 7,951 househ olds from 10.327 house holds in the Puskesmas Kaliwates show slatrine ownership of 66.06%. This research purpose to descri be the basic elementary management of house hold waste in the Kaliwates Sub-District in Jember. This researchis a descriptive study. The method used in this study is the observation and interviews with 40 responden and sampling method was carried out by using a purposive sampling technique. The results sho wed that for elementary sanitation facilities associated with waste disposal, management of house hold waste, means of excreta disposal and management of stoolis still in the low category. Keyword: Elementary Sanitation, Household Waste Management